Renal dysfunction can occur in advanced‐stage Duchenne muscular dystrophy. Issue 2 (28th November 2019) - Motoki, Takahiro; Shimizu‐Motohashi, Yuko; Saito, Isao; Komaki, Hirofumi; Ishiyama, Akihiko; Aibara, Kaori; Jogamoto, Toshihiro; Tezuka, Yuko; Kawabe, Mika; Makino, Akira; Nagatani, Koji; Tatara, Katsunori; et al.
Abstract: Introduction: With improved treatments, patients with Duchenne muscular dystrophy (DMD) can survive far beyond adolescence. However, advanced‐stage DMD patients are at risk of developing renal dysfunction. In this study, long‐term renal function outcomes and associated risk factors in advanced stage DMD were analyzed. Methods: Fifty‐one patients were classified into three different age groups (<20, 20–29, and ≥30 years of age), and cystatin C (CysC) levels were compared among groups. Results: Median serum CysC levels were 0.74 mg/L, 0.63 mg/L, and 0.76 mg/L in the age groups of <20, 20–29, and ≥30 years, respectively ( P = .003). Five of the nine patients in the ≥30 years age group showed elevated serum CysC and decreased cardiac function compared with the other four in the group ( P = .014). Discussion: Our results indicate an association between cardiac and renal dysfunction in patients with advanced‐stage DMD.